4g+7-3G=9

Simple and best practice solution for 4g+7-3G=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4g+7-3G=9 equation:


Simplifying
4g + 7 + -3G = 9

Reorder the terms:
7 + -3G + 4g = 9

Solving
7 + -3G + 4g = 9

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -3G + -7 + 4g = 9 + -7

Reorder the terms:
7 + -7 + -3G + 4g = 9 + -7

Combine like terms: 7 + -7 = 0
0 + -3G + 4g = 9 + -7
-3G + 4g = 9 + -7

Combine like terms: 9 + -7 = 2
-3G + 4g = 2

Add '-4g' to each side of the equation.
-3G + 4g + -4g = 2 + -4g

Combine like terms: 4g + -4g = 0
-3G + 0 = 2 + -4g
-3G = 2 + -4g

Divide each side by '-3'.
G = -0.6666666667 + 1.333333333g

Simplifying
G = -0.6666666667 + 1.333333333g

See similar equations:

| 4x+8=9x+11 | | 47=7(z-3) | | 47=7(2-3) | | A/0.2=-2.6 | | b+3=2x | | 8(1+m)+3=2(m-5.50) | | (-21)-q=(-6) | | x+47=114 | | 6.8+k=6.8+k | | 1/4x-2y=-3/4 | | 3(6x-2)=180 | | X+(x+6499)=210355 | | 1.5t+6=7 | | 7x+10=5z-9 | | -7x+7(-2+10)=-56 | | 12x-8=2x+42 | | A1/2=-5-12 | | 15/2h=5/12 | | 8/16÷5/39 | | (-30)=w+(-14) | | -7+5x=-43 | | -2-4x+6-5x=-9x-4 | | 19x+13y=3 | | -5+2x=12 | | 3x-3(2x-6)=-6 | | n/2-12=2 | | 3x+2x=-5x-10 | | -4(7x-1)=-24 | | 35=b+17 | | 1.5+6=7 | | 8x^3/x-5 | | 8-14z=-24+12z |

Equations solver categories